An Optimized Box-Behnken Design RP-HPLC Method For The Quantification Of Umiclinidinium Bromide And Vilanterol Trifenate In Oral Inhalation - TATAPUDI, HEMANT KUMAR; Bairam, Ravinder; Kassireddy, Vanaja; Mohammed, Rukkiya Jabeen; Baithi, Ankitha; Yata, Sowmya (Drug Analytical Research, 2024)
A liquid chromatographic method with enhanced efficacy has been proposed for the simultaneous quantification of Vilanterol Trifenate and Umiclinidinium Bromide in pharmaceutical formulation. This method is straightforward, sensitive, accurate, precise, and dependable. The RP-HPLC method’s experimental parameters were multivariately optimized using the design of experiments (DoE). Mathematical models were created using three independent variables: the percentage of acetonitrile, the strength of the buffer, and the pH of the mobile phase. In order to examine the response surface methodology and the effects of these independent factors, a box-behnken design (BBD) was utilized. The optimized and forecasted data from the contour diagram utilized a mixture of acetonitrile (58.6% v/v) and phosphate buffer (12.6 mM) with a pH of 5.1. The flow rate was adjusted to 1 milliliter per minute and the analytical wavelength employed was 272 nm. The pharmaceuticals were successfully separated with high resolution in less than 6 minutes under ideal conditions, and the validation process was conducted in accordance with the requirements set by the International Council for Harmonisation (ICH). The findings indicated that the Quality by Design technique was effective in optimizing the RP-HPLC method for quantifying Vilanterol Trifenate and Umiclinidinium Bromide.